2017
DOI: 10.1371/journal.pntd.0005241
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Intra-Nuclear Trafficking of Burkholderia pseudomallei: Strategies of Evasion from Immune Surveillance?

Abstract: BackgroundDuring infection, successful bacterial clearance is achieved via the host immune system acting in conjunction with appropriate antibiotic therapy. However, it still remains a tip of the iceberg as to where persistent pathogens namely, Burkholderia pseudomallei (B. pseudomallei) reside/hide to escape from host immune sensors and antimicrobial pressure.MethodsWe used transmission electron microscopy (TEM) to investigate post-mortem tissue sections of patients with clinical melioidosis to identify the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…By contrast, high antibody titres detected in patients years after an episode of acute melioidosis suggest continuous exposure or covert sequestration (bacteria hiding in cryptic sites with downregulation of products) 91 . B. pseudomallei has been found within the nucleus, which could potentially act as a persistence site for later recrudescence 92 . Strain variability or small colony variants could also play a part in determining whether latent or persistent infection is established 93 .…”
Section: B Pseudomallei Infectionmentioning
confidence: 99%
“…By contrast, high antibody titres detected in patients years after an episode of acute melioidosis suggest continuous exposure or covert sequestration (bacteria hiding in cryptic sites with downregulation of products) 91 . B. pseudomallei has been found within the nucleus, which could potentially act as a persistence site for later recrudescence 92 . Strain variability or small colony variants could also play a part in determining whether latent or persistent infection is established 93 .…”
Section: B Pseudomallei Infectionmentioning
confidence: 99%
“…BipC, an immunoreactive protein, is involved in actin binding to facilitate internalization of B. pseudomallei into host cells, as a bipC mutant was impaired in adherence, invasion, and intracellular survival in epithelial cells, and BipC protein is required for full virulence in a murine model of melioidosis [ 78 , 79 ]. Recently, Vadivelu et al [ 80 ] showed that B. pseudomallei localized within the nuclear compartment of host cells, suggesting that the nucleus may play a role as an occult or transient niche for persistence of intracellular pathogens, potentially leading to recurrent episodes or recrudescence of infection.…”
Section: Molecular Pathogenesis Of B Pseudomalleimentioning
confidence: 99%
“…Future experiments should thus reveal the mechanisms of persistent haemoplasma infection. In particular, it is important to understand whether (a) the low stable infection levels result from the bacterium's or the mammalian host's actions, (b) the bacterium hides in other tissues in the rodent's body (Novacco, Riond, Meli, Grest, & Hofmann-Lehmann, 2013;Tasker et al, 2009a;Wolf-Jäckel et al, 2012), and (c) the bacterium replicates during the stabilized infection period or remains in a dormant state (Mandell & Beverley, 2017;Monack & Hultgren, 2013;Potgieter, Bester, Kell, & Pretorius, 2015;Vadivelu et al, 2017).…”
Section: Infection Dynamicsmentioning
confidence: 99%